Vai trò của chất lượng dịch vụ logistics trong thương mại điện tử đối với sự hài lòng và lòng trung thành của khách hàng Gen Z tại thị trường Hà Nội - Vũ Phương, Thảo; Vũ Tuấn, Dương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study aims to evaluate the influence of the logistics service quality (LSQ) in e-commerce on customer satisfaction and customer loyalty of Gen Z in Hanoi. The research results from 392 customers indicated that the LSQ includes three components: Timeliness, availability, and condition of the purchase orders. While condition and availability of purchase orders positively affect customer satisfaction and loyalty, timeliness does not show a driving role for the two dependent variables. Finally, satisfaction is proven to have a predictability on customer loyalty of Gen Z. From these findings, several implications are proposed to help businesses improve LSQ, customer satisfaction, and customer loyalty.